Health and associated economic benefits of reduced air pollution and increased physical activity from climate change policies in the UK - Heather Walton; David Dajnak; Mike Holland; Dimitris Evangelopoulos; Dylan Wood; Christian Brand; Nosha Assareh; Gregor Stewart; Andrew Beddows; Shawn YC Lee; Daniela Fecht; Yunzhe Liu; et al. (Environment International)
Climate change policies do not always include analysis of air quality and physical activity co-benefits. We compared business as usual (BAU) UK policy with Net Zero scenarios from the UK Climate Change Committee for road transport and building sectors. We quantified and monetised the health benefits of the Balanced Net Zero (BNZP) and Widespread Innovation (WI) Pathways.Air pollution concentrations were predicted using Chemical Transport Models and population-weighted. Shifts from car to walking and cycling for transport were converted to METhrs/week. Literature concentration–response functions were combined with baseline rates from routine statistics/other sources. Mortality and multi-morbidity impacts were calculated using lifetable analysis, and an incidence/prevalence model from 2019 to 2154 (a lifetime after 2050). Monetary values were applied to the results.The BNZP policy compared with BAU gave 4.9 (95 % confidence interval 1.0–9.0) million life-years gained (LYG) (UK population, to 2154), including 1.1 (0.7–1.6) million LYG from active travel improvements. Avoided COPD and childhood asthma cases were 201,000 (150,000 – 250,000) and 192,000 (64,600–311,000). The monetised air quality morbidity benefits (£52.1 (36.4 – 67.8) billion) substantially added to the air quality mortality benefits (£77.9 (42.9 to 90.8) billion). Total yearly monetised benefits for BNZP vs BAU summed to 2154 (air pollution/active travel) were £153 (122 to 184) billion (core); 278 (228 to 334) billion (+outcomes with weaker evidence).Adding the effects of air pollution reductions on disease incidence, with effects of air pollution and physical activity on mortality, increases the monetised benefits that may justify Net Zero policies in cost-benefit analysis.